The genetic variations in SAP97 gene and the risk of schizophrenia in the Chinese Han population: a further study. (August 2020) - Xu, Xusan; Wang, Yajun; Zhou, Xia; Yin, Jingwen; Yu, Huajun; Wen, Xia; Lv, Dong; Zhu, Dongjian; Xiong, Susu; Yan, Haifeng; Dai, Zhun; Lin, Zhixiong; et al.
Abstract : Background and Methods: Based on our previous discovery that SAP97 rs3915512 polymorphism significantly affects the cognitive function of schizophrenia, we further genotyped the other 12 single-nucleotide polymorphisms (SNPs) capturing the known common haplotype variations of this gene in a sample including 1014 patients with schizophrenia and 1078 matched controls. Results: There were no significant differences in the distribution of genotypes and alleles of the 12 SNPs of SAP97 between the patients and the controls (all P > 0.05). But, in the evaluation of the phenotypic effects of these SNPs on the patients' clinical symptoms and cognitive functions. While patients with minor allele in the rs9843659 polymorphism had higher N5 (difficulty in abstract thinking) scores than that with the main genotype ( P = 0.002, Pcor = 0.014), the patients with minor allele in the rs6805920, rs4916461 and rs7638423 had lower verbal memory scores ( P = 0.003, 0.003, 0.001, Pcor = 0.021, 0.021, 0.007, respectively) and the P values of these SNPs were still significant after the Bonferroni correction. Conclusion: Our data are further to indicate that the SAP97 gene polymorphisms may affect neurocognitive function especially verbal memory and the first to suggest that the SAP97 rs9843659 polymorphism may influence abstract thinking of schizophrenic patients in the southern Han Chinese population. Abstract : Supplemental Digital Content is available in the text.